Rust fungi (Pucciniales) on Cyperaceae in Japan, with 2 new names, 5 new combinations and typifications - Kakishima, Makoto; Ji, Jing Xin; Hosaka, Kentaro; Hosoya, Tsuyoshi (Phytotaxa, 2024)
Rust fungi (Pucciniales) producing uredinial and/or telial stages on species of Cyperaceae in Japan are listed based on literature records. Host plants and distribution of 92 species (86 species of Puccinia, 5 species of Uromyces and 1 species of Uredo) are described. Among them two new names and five new combination names are proposed in accordance with the Shenzhen Code, ICNafp. Type specimens (neotypes, lectotypes, epitypes, paratypes) for 29 species are selected and designated. One hundred species of Cyperaceae (22.9% of species reported in Japan) including ten genera are recorded as their host plants of uredinial and/or telial stages. Spermogonial and aecial stages of 36 species are confirmed and 59 species of plants including 14 families 29 genera are also described as their hosts.